Biometric relationships of the deep-water velvet shrimp Metapenaeopsis sibogae (De Man, 1907) (Crustacea: Decapoda: Penaeidae) in Kagoshima Bay, Japan. Issue 4 (2nd October 2018) - Rahman, Md. Mosaddequr; Ohtomi, Jun
ABSTRACT: Metapenaeopsis sibogae (De Man 1907) is a newly recorded shrimp in Japanese waters and is an emerging fisheries resource. We studied the biometric relationships of M. sibogae in Kagoshima Bay, southern Kyushu, Japan using samples collected during January to December 2014. The overall sex ratio differed significantly from a 1:1 favoring the males. A predominance of males was observed in the smaller carapace length (CL) classes whereas the upper end is increasingly occupied by females. The CL and body weight (BW) of females were significantly larger than those of the males. The relationship between BW and CL indicated negative allometric growth in both sexes and the intercept and slope of the regression lines between the sexes differed significantly. The growth rate of BW to CL was significantly lower in maturing and mature females than that in the immature females. The condition factor of females was higher than that of the males probably because of higher growth rate in males, which resulted in reduced energy accumulation. Significantly lower values of condition factor were recorded for the maturing and mature females than that of the immature females, which probably indicating extra energy allocation for reproduction in these stages.